Encapsulating C59N azafullerenes inside single-wall carbon nanotubes - Simon, F.; Kuzmany, H.; Fülöp, F.; Jánossy, A.; Bernardi, J.; Hauke, F.; Hirsch, A. (Physica Status Solidi (b), 2006)
Filling of single‐wall carbon nanotubes with C59N azafullerene derivatives is reported from toluene solvent at ambient temperature. The filling is characterized by high resolution transmission electron microscopy and Raman spectroscopy. The tube–azafullerene interaction is similar to the tube–C60 interaction. The encapsulated C59N monomer radical is observed using electron spin resonance spectroscopy after vacuum annealing of the azafullerene derivatives. (© 2006 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)